SENSITIVITY OF BIOFILM-PRODUCING BACTERIA FROM NASOGASTRIC TUBES TO ANTIBIOTICS CEFTRIAXONE & CEFOBACTAM - Tolulu, Sri Noviani; Rasdianah, Nur; Pakaya, Mahdalena Sy.; Madania; Uno, Wiwit Zuriati (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2025)
Nasogastric Tube (NGT) is a common practice in medical care, especially for the administration of nutrients or drugs directly into the digestive tract. The surface of the NGT is in direct contact with the respiratory tract and digestive tract providing ideal conditions for bacteria to form biofilms. Biofilms have the ability to provide a high level of resistance to antimicrobial action and body defenses. Biofilms provide a microenvironment that protects bacteria from direct exposure to antimicrobial agents, such as antibiotics. This study aims to determine the sensitivity of biofilm-producing bacteria from NGT to antibiotics. This study used an experimental method conducted in the Pharmaceutical Microbiology Laboratory using purposive sampling techniques, biofilm detection using the Congo Red Agar and tube methods, Ceftriaxone and Cefobactam antibiotic sensitivity tests using the disc diffusion method. The results obtained that the positive Nasogastric Tube device can produce biofilm bacteria and can affect bacteria to become more resistant to antibiotics for long-term use of the Nasogastric Tube device. It can be seen that the measurement of the inhibition zone shows that the Ceftriaxone antibiotic has an average inhibition zone of 2.32 mm and Cefobactam 7.42 mm.